Strategi Pondok Pesantren Dalam Meningkatkan Proses Belajar Siswa Di Pondok Pesantren Nida Al-Qur’an Temanggung - Maghribi, Saksana Permana; Mujahadah, Kharis Syuhud (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Pondok Pesantren Nida Al-Qur’an Temanggung is an Islamic educational institution that integrates the national curriculum with the traditional boarding school curriculum to improve the quality of students’ learning process. The study aimed to analyze the learning strategies applied in this boarding school, which included the development of traditional and modern learning methods. The approach used in this study was a descriptive qualitative approach with data collection techniques through observation, interviews, and documentary study. The study also analyzed the supporting and hindering factors affecting the implementation of learning strategies in Nida Al-Qur’an Temakgo Boarding School. The results of the study showed that Nida Al-Qur’an Temanggung Boarding School successfully developed a learning system that combined the methods of sorogan, banndongan, halaqah, and technology-based learning. The applied curriculum integrates religious sciences and general sciences, creating students with academic ability as well as good life skills. Additionally, character coaching strategies and educators’ competencies are also a major focus in improving the quality of education. However, challenges such as limitations of technological infrastructure and differences in students’ beginning abilities become inhibiting factors in the learning process. In conclusion, the learning strategies applied in Nida Al-Qur’an Temanggung Boarding House showed success in creating a learning process adaptive to the development of the times. Despite facing several challenges, this boarding school continues to innovate in creating effective and sustainable learning models without compromising traditional Islamic values. This study makes a practical contribution for future development of learning strategies in boarding schools.